2020
DOI: 10.2174/1874331502014010339
|View full text |Cite
|
Sign up to set email alerts
|

Combined Influence of Chitosan and Calcium Chloride on Fusarium Dry Rot Disease Under Field Conditions

Abstract: Background: Fusarium dry rot disease caused by Fusarium sambucinum Fuckel (F. sambucinum) can infect the potato tubers in the field and during storage. Yield losses by F. sambucinum reach 60%. Traditional methods to control Fusarium dry rot are fungicides application, which led to developing many isolates resistant to these fungicides. Objective: The aim of this study is to evaluate the effect of calcium chloride (CaCl2) and chitosan, alone or in combination, on plant developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In fact, the 6 kg/ha CaCl 2 treatment showed similar values of yield relative to the control, while 3 kg/ha CaCl 2 treatment only showed a 3.4% increase in the yield. Indeed, our data are not in accordance with a previous study that used two foliar sprays containing 2 and 4 kg/ha of CaCl 2 , which enhanced the tuber yield [13], or even according to another study carried out by [14], which showed improvements in tuber yield resulting from foliar sprays containing calcium chloride. Furthermore, the third treatment with the highest Ca content (2 kg/ha Ca(NO 3 ) 2 treatment) (Figure 1) was the one with the highest yield (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, the 6 kg/ha CaCl 2 treatment showed similar values of yield relative to the control, while 3 kg/ha CaCl 2 treatment only showed a 3.4% increase in the yield. Indeed, our data are not in accordance with a previous study that used two foliar sprays containing 2 and 4 kg/ha of CaCl 2 , which enhanced the tuber yield [13], or even according to another study carried out by [14], which showed improvements in tuber yield resulting from foliar sprays containing calcium chloride. Furthermore, the third treatment with the highest Ca content (2 kg/ha Ca(NO 3 ) 2 treatment) (Figure 1) was the one with the highest yield (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
“…A such, this suggests that, despite not displaying a higher NDVI value or even a significant increase in Ca in the tubers, CaCl 2 applied at a 12 kg/ha concentration showed a positive effect in promoting yield enhancement in tubers of Solanum tuberosum L. (Agria variety). Furthermore, even with the same food matrix (potatoes), other studies carried out with different varieties [19][20][21] showed higher yields with Ca foliar applications. However, according to our findings, the increase in yield with Ca foliar applications is dependent on the Ca products being applied and their concentration (Figure 2 and Table 2).…”
Section: Discussionmentioning
confidence: 86%
“…However, chemicals such as arachidonic acid and chitosan, abscisic acid, Scarvone, and aminotriazole were used as regulators for wound healing (Ozeretskovskaya et al, 2009;Woolfson, 2018). Calcium chloride has been used to prevent and control potato diseases (Mohammed et al, 2020). Salicylic acid and calcium chloride are also used to control budding in tuber (Mushtaq et al, 2019).…”
Section: Firming Agentsmentioning
confidence: 99%